Choledochoduodenal fistula: An unusual cause of recurrent cholangitis in children - Duman, Levent (Medknow Publications & Media Pvt Ltd, 2014)
Choledochoduodenal fistula (CDF) is an unusual clinical entity and a diagnostic challenge in children. We herein present CDF as an unusual cause of recurrent cholangitis in a 6-year-old child. To the best of our knowledge, this is the youngest patient reported until date. In this paper, we also highlight possible etiologic factors, presenting symptoms, diagnostic methods, and treatment modalities of CDF.